Revision and cladistic analysis of the genus Ptychoderes Schoenherr, 1823 (Coleoptera, Anthribidae, Anthribinae, Ptychoderini) - Mermudes, José Ricardo M.; Napp, Dilma Solange (Zootaxa, 2006)
A review and cladistic analysis of the genus Ptychoderes Schoenherr, 1823 is presented. The genus and the following seventeen known species are redescribed: P. nebulosus (Olivier, 1795) (type species), P. elongatus (Germar, 1824), P. viridanus Boheman, 1833, P. virgatus Fåhraeus, 1839, P. obsoletus Jekel, 1855, P. depressus Jekel, 1855, P. mixtus Jekel, 1855, P. callosus Jekel, 1855, P. antiquus Jekel, 1855, P. brevis Jordan, 1894, P. longicollis Jordan, 1894, P. bivittatus Jordan, 1894, P. rugicollis Jordan, 1895, P. jordani Frieser, 1959, P. crustatus Frieser, 1988, P. magnus Mermudes & Napp, 2004 and P. jekeli Mermudes & Napp, 2004. New synonyms are proposed: Ptychoderes nebulosus (Olivier, 1795) = Ptychoderes tricostifrons Fåhraeus, 1839 syn. nov. = Ptychoderes columbianus Jekel, 1855 syn. nov.; and Ptychoderes antiquus Jekel, 1855 = Ptychoderes affinis Jordan, 1894 syn. nov. A key to species and maps of their geographical distribution are provided. The cladistic analysis with 24 taxa and 50 characters from body vestiture, external morphology, wing venation, male and female terminalia and rectal loop, resulted in a single cladogram showing, for the first time, a hypothesis of phylogenetic relationship among genera of Anthribinae. The analysis included the seventeen species of Ptychoderes, as defined in the taxonomic review, along with the type species of the genera presently considered as belonging to Ptychoderini Jekel, 1855: Cerambyrhynchus schoenherri Montrouzier, 1855, Phloepemon acuticornis (Fabricius), Phloeotragus heros (Fabricius), Tribotropis prasinata (Fåhraeus, 1839), Hypselotropis annulicornis (Fåhraeus, 1839) and Unanthribus maximus Mermudes, 2003. A hypothesis of the phylogenetic relationships among the Neotropical genera of Ptychoderini is presented in parenthetical notation: ((Tribotropis + Hypselotropis) (Unanthribus + Ptychoderes)). The monophyly of Ptychoderes is supported by 14 synapomorphies and its interrelationships are as follows: ((P. crustatus (P. brevis + P. jekeli)) ((P. longicollis (P. jordani (P. obsoletus+P. magnus) (P. depressus+P. virgatus))) (P. mixtus (P. bivittatus ((P. callosus+P. rugicollis) (P. viridanus (P. antiquus (P. elongatus+P. nebulosus)))))))).